2015
DOI: 10.1002/stem.1857
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: The Obesity Cancer Paradigm: Exploration of the Interactions and Crosstalk with Adipose Stem Cells

Abstract: With the recognition of obesity as a global health crisis, researchers have devoted greater effort to defining and understanding the pathophysiological molecular pathways regulating the biology of adipose tissue and obesity. Obesity, the excessive accumulation of adipose tissue due to hyperplasia and hypertrophy, has been linked to an increased incidence and aggressiveness of colon, hematological, prostate, and postmenopausal breast cancer cancers. The increased morbidity and mortality of obesity-associated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 140 publications
(177 reference statements)
1
77
0
3
Order By: Relevance
“…This study demonstrated that there is a wide breadth of available literature on the relationship between ASCs and cancer development, including mounting evidence in the areas of ASCs' role in the growth, progression, and metastasis of various malignancies (82)(83)(84). It appears that ASCs potentially play a role in multiple processes affecting tumor microenvironment; however, few articles specifically address the influence of ASCs on tumor microenvironment.…”
Section: Resultsmentioning
confidence: 88%
“…This study demonstrated that there is a wide breadth of available literature on the relationship between ASCs and cancer development, including mounting evidence in the areas of ASCs' role in the growth, progression, and metastasis of various malignancies (82)(83)(84). It appears that ASCs potentially play a role in multiple processes affecting tumor microenvironment; however, few articles specifically address the influence of ASCs on tumor microenvironment.…”
Section: Resultsmentioning
confidence: 88%
“…HGF, pg/ml Adiponectin, ng/ml Leptin, pg/ml cancer cell proliferation, motility and overall cancer progression (25). Previous studies revealed that circulating leptin levels positively correlate with adiposity (11,38).…”
Section: Hgf Pg/mlmentioning
confidence: 96%
“…Obesity is a global health problem associated with a variety of metabolic diseases (24) and, at present, obesity is an established risk factor for epithelial tumors (25)(26)(27). Obesity is characterized as an excess of adipose tissue and defined by a BMI ≥30 kg/m 2 according to the WHO criteria (7).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations